Gender disparities in the education gradient in self-reported health across birth cohorts in China - Bowen Zhu; Yiwan Ye (BMC, 2020)
Abstract Background Variation in the relationship between education and health has been studied intensely over the past few decades. Although there is research on gender disparity and cohort variations in educational effect on health using samples from the U.S. and Europe, research about China's is limited. Given the specific social changes in China, our study is designed to analyze the gender and cohort patterns in the education-health gradient. Method The latent growth-curve modeling was used to analyze the gender and cohort variations in the education gradient in self-rated health among Chinese respondents. The study employed longitudinal and nationally representative data from the Chinese Family Panel Studies from the years 2010 to 2016. Each cohort is specified according to their distinct periods of social change in China. Following the analysis, we used latent growth-curve model to illustrate gender and cohort differences in the age-graded education and health trajectories. Results Although Chinese men have reported to have better health than women in general, women reported 1.6 percentage points higher in self-reported health for each additional year of schooling compared to that of men (P < 0.001). The latent growth curve model showed women's extra education benefits were persistent overtime. Compared to the people born during the "Old China" (1908-1938), the education gradient in self-rated health did not change for cohorts born before 1955 and after 1977, but the education-health gap changed significantly in the 1956-1960 (O.R. = 1.038, P < 0.05), 1967-1976 (O.R. = 1.058, P < 0.001), and 1977-1983 (O.R. = 1.063, P < 0.001) cohorts. There was a gender difference for the cohort variations in the education-health gradient. For women, the education effect in the 1956-1960 (O.R. = 1.063, P < 0.05), 1967-1976 (O.R. = 1.088, P < 0.001) and 1977-1983 (O.R. = 1.102, P < 0.001) cohorts was significantly higher than that of the 1908-1938 cohort. On the contrary, the education-health gradient remained the same across all cohorts for men. Conclusion Our study suggests that the education-health gradient varies across cohorts for women, but the size of education effect remains consistent for men across cohorts. The findings support the resource-substitution hypothesis and not the rising-importance hypothesis in China. We discussed the potential influences of the unique, social transformation and educational expansion in China.